2013
DOI: 10.1021/ja409421d
|View full text |Cite
|
Sign up to set email alerts
|

β-Ketoenamine-Linked Covalent Organic Frameworks Capable of Pseudocapacitive Energy Storage

Abstract: Two-dimensional covalent organic frameworks (2D COFs) are candidate materials for charge storage devices because of their micro- or mesoporosity, high surface area, and ability to predictably organize redox-active groups. The limited chemical and oxidative stability of established COF linkages, such as boroxines and boronate esters, precludes these applications, and no 2D COF has demonstrated reversible redox behavior. Here we describe a β-ketoenamine-linked 2D COF that exhibits reversible electrochemical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
740
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,052 publications
(770 citation statements)
references
References 35 publications
21
740
1
8
Order By: Relevance
“…Due to 12 their permanent porosity, structural periodicity and high thermal 13 stability, COFs have triggered substantial research interest over the 14 past decade for potential applications in gas storage and separation 15 [4][5][6][7][8][9], catalysis [10,11], sensing [12,13], optoelectronic devices 16 [14,15] and energy storage [16][17][18]. Two-dimensional (2D) COFs, 17 in which the 2D polymer sheets stack in a columnar manner to 18 form a layered eclipsed structure [19], provide a unique means to 19 construct ordered p systems for efficient charge carrier transport 20 through the framework and have potential for developing new p- 21 electronic and photofunctional materials [20].…”
mentioning
confidence: 99%
“…Due to 12 their permanent porosity, structural periodicity and high thermal 13 stability, COFs have triggered substantial research interest over the 14 past decade for potential applications in gas storage and separation 15 [4][5][6][7][8][9], catalysis [10,11], sensing [12,13], optoelectronic devices 16 [14,15] and energy storage [16][17][18]. Two-dimensional (2D) COFs, 17 in which the 2D polymer sheets stack in a columnar manner to 18 form a layered eclipsed structure [19], provide a unique means to 19 construct ordered p systems for efficient charge carrier transport 20 through the framework and have potential for developing new p- 21 electronic and photofunctional materials [20].…”
mentioning
confidence: 99%
“…Unlike the reaction that occurred in solution, fabricating low dimensional COF at the liquid/solid or gas/solid interface through self-condensation of boronic acids is a novel method to form a series of nanomaterials equipped with functional characteristics such as sensing [38,39], energy storage [40], optoelectronic devices [41,42], and catalysis [43,44]. The building blocks of the condensation equipped with more than two functional groups, hydroxide radical, is a basic precondition to trigger the reaction, and the ambient environment around the reaction monomers can obviously decide the quality of the surface covalent organic framework (SCOF).…”
Section: Self-condensation Of Boronic Acidsmentioning
confidence: 99%
“…However, only 2.5 % of the anthraquinone moieties was accessed in this 2D COF slurry modified electrode, which was attributed to the random orientation of polycrystalline COF particles and nonoptimal interface to the bulk electrode. 12 In one of our recent work we have demonstrated that single layer 2D COF can be synthesized on graphene surface through on-surface condensation between aromatic aldehyde and amine. 13 DFT simulations have confirmed the strong interaction and significant electron band mixing between the well oriented single layer COF and graphene.…”
mentioning
confidence: 99%